Enhancing Health Outcomes for Breastfeeding Mothers and Children Through Optimal Nutrition – A Narrative Review - Wasito, Erika (Journal of Indonesian Specialized Nutrition, 2024)
Breastfeeding is one of the best ways to provide nutrition to babies. Apart from that, breastfeeding also provides many benefits for health, such as reducing the risk of breast and ovarian cancer. However, not all mothers can breastfeed optimally, this can be caused by various factors. This review aims to discuss the role of nutrition in improving the health of breastfeeding mothers and children. Research results show that ensuring breastfeeding mothers receive sufficient nutrition to support healthy breast milk production can improve health outcomes for both mother and child. There are various factors that affect the nutritional intake of breastfeeding mothers, including knowledge about breastfeeding nutrition, dietary habits, the mother's busy activity, and social support. Adequate nutrition during the breastfeeding period can significantly reduce the likelihood of mothers suffering from fatigue, anemia, and depression. Similarly, infants who receive sufficient breast milk are less likely to experience stunting, infections, and other chronic illnesses.